Features of the development of Acanthoscelides obtectus (Say, 1831) (Coleoptera: Chrysomelidae: Bruchinae) in different leguminous crops - Sereda, V. A. (The Kharkiv Entomological Society Gazette, 2026)
In laboratory conditions, the features of the development of Acanthoscelides obtectus (Say) on eight species of potentially host plants (Phaseolus vulgaris L., Ph. lunatus L., Vigna radiata (L.), V. unguiculata subsp. sesquipedalis (L.), Cicer arietinum L., Pisum sativum L., Glycine max (L.), Lens culinaris L.) were investigated. A relationship was established between the length of the seed of the host plant and the size of the pest’s adult. The optimal host species is Ph. vulgaris. C. arietinum, V. radiata, V. unguiculata, and Ph. lunatus were identified as alternative host plants for this bruchid species. Seeds of P. sativum and L. culinaris turned out to be of little use for the development of the bean weevil, and G. max was unsuitable. The differentiated trophic specialization of the bean weevil and the importance of taking into account the type of host plant when storing legume crops were confirmed. 1 fig, 5 tabs, 27 refs.